Reference conditions for rehabilitating mine stockpiles as novel upland ecosystems in Canada’s subarctic - Garrah, KL; Campbell, D (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
In Canada’s subarctic Hudson Bay Lowlands, mining activity is creating stockpiles of processed kimberlites and other non-acid generating materials that must be rehabilitated to novel upland ecosystems dominated by native plant species. Reclaiming these piles to regionally compatible, productive and self-sustaining ecosystems first requires an understanding of edaphic factors, plant communities and soil-plant relationships on analogous natural environments. Currently, little is known about these factors and relationships on existing uplands in this region. Vegetation and soil characteristics were sampled along a natural successional gradient of well-drained riverbank sites near the De Beers Victor Mine, Ontario, Canada. One plot per sere per site was sampled, up to three seres at each site. Isolated natural uplands were similarly examined along a 150 km east-west geological chronosequence beginning at James Bay. Two plots were samples per feature as accessibility permitted. Sampling reflected that of the forest ecosystem classification program in northern Ontario, in which (i) vegetation in a 10 × 10 m plot was described at each site, and (ii) soils were determined by describing a soil pit. Parameters of interest included vegetation structure and cover, species richness and species composition, forest mensuration (height, diameter at breast height, age) and soil physical and chemical characteristics. Descriptive statistics were calculated for all quantitative variables. Relationships among site types were analysed using cluster analysis, principal components analysis and non-metric multi-dimensional scaling. The four objectives of this study are to (i) describe the mean and range of conditions of the observed plant and soil parameters, (ii) group sites by common plant and soil characteristics, iii) group plant assemblages in seres, and (iv) construct a set of reference conditions. This technical paper includes a representative sample of the results of the ongoing MSc thesis described above.